Physical Therapist Student Readiness for Entrance Into the First Full-Time Clinical Experience: A Delphi Study. Issue 2 (17th December 2018) - Timmerberg, Jean F; Dole, Robin; Silberman, Nicki; Goffar, Stephen L; Mathur, Divya; Miller, Amy; Murray, Leigh; Pelletier, Deborah; Simpson, Michael S; Stolfi, Angela; Thompson, Anne; Utzman, Ralph
Abstract: Background: To consistently prepare physical therapist students for their first full-time clinical experience, the entry-level curriculum must provide and assess competency in the essential knowledge, skills, attitudes, and professional behaviors. Objective: The purpose of this Delphi study was to develop consensus on a core set of elements that should be demonstrated by physical therapist students prior to entry into their first full-time clinical experience. A second aim was to obtain the recommended competency levels and assessment methods. Design: The study was conducted using the Delphi method. Methods: Purposive selection and snowball sampling techniques were used to recruit clinical instructors, recent graduates, directors or academic coordinators of clinical education, and academic faculty. Four web-based survey rounds were used to achieve consensus, defined as agreement among ≥80% of respondents. The first round gathered demographic information on respondents and identified elements that were deemed essential; the second collected information about clarity and redundancy in the elements provided; the third asked participants to rank their agreement with elements and themes; and the fourth gathered the level of competency that physical therapist students should demonstrate prior to beginning a first full-time clinical experience. Results: Consensus revealed 95 elements, categorized under 14 themes, which were deemed essential for readiness for the first clinical experience. Levels of competency for each element were identified. Limitations: Participants might not have represented all academic programs, practice settings, and geographic locations. Conclusion: This study identified the specific knowledge, skills, attitudes, and professional behaviors in which all physical therapist students in the United States need to demonstrate competency before their first clinical experience, regardless of school or setting, which would allow learning experiences to be tailored appropriately.